Med romantikken i bakspejlet.: Tobias Norlind-föreläsning, Växjö 7 juni 2006 - Møller Sørensen, Søren (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2007)
Romanticism in the rear view mirror The article engages in the discussion of the aesthetics of the German romanticists and the emergence of the concept of the musical work. In many contributions to this debate – most noticeably those of Carl Dahlhaus – German romanticism is pointed out as the main contributor to the development of the work concept. This article argues that the strong link between the romanticists and the aesthetics of the musical work asserted by Dahlhaus and his followers needs to be reconsidered. Apparently we have to do with a kind of anamnesic historiography, where contemporary issues in the historiographer’s intellectual environment too forcefully impose a too narrow perspective. A less biased reading reveals a multifarious and open discourse with relatively little emphasis on the work issue and a delicate attentiveness to immediate sensual qualities of sound.